2011
DOI: 10.2337/dc10-2167
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D, Calcium Intake, and Risk of Type 2 Diabetes After 5 Years

Abstract: OBJECTIVETo examine whether serum 25-hydroxyvitamin D (25OHD) and dietary calcium predict incident type 2 diabetes and insulin sensitivity.RESEARCH DESIGN AND METHODSA total of 6,537 of the 11,247 adults evaluated in 1999–2000 in the Australian Diabetes, Obesity and Lifestyle (AusDiab) study, returned for oral glucose tolerance test (OGTT) in 2004–2005. We studied those without diabetes who had complete data at baseline (n = 5,200; mean age 51 years; 55% were women; 92% were Europids). Serum 25OHD and energy-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
161
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(180 citation statements)
references
References 24 publications
(47 reference statements)
13
161
1
5
Order By: Relevance
“…The recent data from Australian diabetes, obesity and lifestyle study suggests that the 25(OH)D levels were low in diabetes subjects and there was inverse association between 25(OH)D and type 2 diabetes risk in their population [30]. From our case-control study, we observed decreased 25(OH)D levels in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 45%
“…The recent data from Australian diabetes, obesity and lifestyle study suggests that the 25(OH)D levels were low in diabetes subjects and there was inverse association between 25(OH)D and type 2 diabetes risk in their population [30]. From our case-control study, we observed decreased 25(OH)D levels in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 45%
“…They involve the rapid regulation of membrane calcium channels, suggesting a role for vitamin D in the calcium‐mediated muscle functions, such as muscle contraction and mitochondrial function, which leads to an adequate insulin signalling and muscle substrate metabolism 42. All these findings may clarify the relationship between low vitamin D status and muscle weakness,37, 43 intramuscular fat deposition,44 and resistance to insulin,45 which is related to cardiovascular risk and increased skeletal muscle breakdown 46. Of note, skeletal muscle may also act as a storage site for vitamin D, as recently described 10…”
Section: Vitamin D Physiologymentioning
confidence: 98%
“…Indeed, when magnesium alone or along with other dietary factors was added to the models, the calcium --diabetes association was to some extent weakened. 3,4,7 A major strength of our study is the prospective design of included studies, which minimizes the possibility of recall bias and selection bias. Potential limitations include residual confounding due to imprecisely measured or unmeasured factors, self-reported dietary intakes and diabetes diagnoses, and lack of repeated measurements in dietary assessment.…”
Section: Discussionmentioning
confidence: 99%